2015
DOI: 10.1097/md.0000000000000592
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Endoscopic-Assisted Harvesting of Pedicled Freestyle Fasciocutaneous Flaps

Abstract: The endoscopy-assisted technique has been demonstrated in harvesting muscle flaps; however, for pedicled freestyle fasciocutaneous flaps, few studies have applied this technique. We present a surgical procedure utilizing endoscopic-assisted method to identify the perforators of pedicled freestyle fasciocutaneous flaps for the reconstruction of soft tissue defects.From August to December 2012, 9 consecutive patients underwent endoscopic-assisted harvesting of fasciocutaneous flaps for the reconstruction of soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…If the skin graft was harvested from the upper lateral thigh, both scars would be out of sight even when wearing short pants precise designs of flaps based on the location of the perforator vessels once located by the endoscope (Katsuragi-Tomioka, Nakagawa, Yamamoto, Kayano, & Matsui, 2012). It has also allowed for accurate identification of perforators to facilitate perforator-based pedicled free style fasciocutaneous flaps (Huang, Lin, Wu, & Yen, 2015). CO 2 insufflation to create a better optic cavity and using standard laparoscopic equipment has also been described for latissimus dorsi muscle flap harvest (Kiiski, Kaartinen, Kotaluoto, & Kuokkanen, 2017), as well as description of endoscope-assisted harvest of latissimus dorsi muscle free flap in the supine position to facilitate a two-team approach for oral cavity reconstruction (Cha, Jeong, & Ahn, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…If the skin graft was harvested from the upper lateral thigh, both scars would be out of sight even when wearing short pants precise designs of flaps based on the location of the perforator vessels once located by the endoscope (Katsuragi-Tomioka, Nakagawa, Yamamoto, Kayano, & Matsui, 2012). It has also allowed for accurate identification of perforators to facilitate perforator-based pedicled free style fasciocutaneous flaps (Huang, Lin, Wu, & Yen, 2015). CO 2 insufflation to create a better optic cavity and using standard laparoscopic equipment has also been described for latissimus dorsi muscle flap harvest (Kiiski, Kaartinen, Kotaluoto, & Kuokkanen, 2017), as well as description of endoscope-assisted harvest of latissimus dorsi muscle free flap in the supine position to facilitate a two-team approach for oral cavity reconstruction (Cha, Jeong, & Ahn, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Details of the endoscopic technique have been described in the previous report. [5] Briefly, in the beginning, the temporary designed flap was marked on the skin. One 5-mm trocar was then inserted through a 1-cm endoscopic incision (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…[13] In a case report in 2012, Katsuragi-Tomioka et al [4] was the first to apply the endoscopic technique to assist in harvesting fasciocutaneous flaps. Subsequently, Huang et al [5] demonstrated the feasibility of the endoscope-assisted method in identifying perforators of fasciocutaneous flaps for 9 consecutive patients. Both Katsuragi-Tomioka et al [4] and Huang et al [5] commented that the endoscope-assisted method could provide a precise flap design and reduce the sacrifice of donor sites because the perforator was directly localized by endoscopic vision.…”
Section: Introductionmentioning
confidence: 99%